PENGARUH KOMPETENSI PROFESIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASIONAL (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the influence of "The Effect of Professional Competence and Organizational Commitment to Teacher’s Performance with Organizational Cultures as a Moderated Variabel". In this study population of 207 people, whereas samples taken as many as 136 people as respondents purposive sampling method. Criteria UPT all public servants in the Department of Education and Culture District of Talun. Measurements using a Likert scale of 5 (five) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) professional competence positive and significant impact on teacher performance, (ii) organizational commitment does not affect the performance of teachers, (iii) organizational culture positive and significant impact on teacher performance, (iv) organizational culture does not moderate the influence of professional competence working with teacher performance, and (v) organizational culture does not moderate the influence of organizational commitment to work with the teacher's performance.Keywords: Professional Competence, Organizational Commitment, Organizational Culture and Performance Teachers.